Pengaruh Orientasi Pasar terhadap Nilai Inovasi, Keunggulan Bersaing, Kinerja Unit Usaha dan Jasa Berbasis Syari’ah. (Studi Kasus unit Usaha dan Jasa berbasis Syari’ah di Wilayah Malang Raya) - Syahirul Alim (El Dinar, 2018)
The marketing concept states that to achieve organizational goals such as market share and profitability depends on the company's ability to determine the needs and wants of the target market and satisfy it more effectively and efficiently than its competitors.The purpose of this study is to examine whether pangaruh between market orientation, innovation value and competitive advantage to the performance of business units and services based on sharia. The results of statistical tests show that market orientation has a significant influence on the value of innovation. Market orientation with competitive advantage has significant influence. The value of innovation with competitive advantage has significant influence. The market orientation with the performance of sharia-based business units and services has no significant effect. This study proves that the value of innovation and competitive advantage is the intervening variable to create the performance of shariah-based business units and services.